Building citizenship: civics and economics - Remy, Richard C.; Patrick, John J.; Saffell, David C.; Clayton, Gary E. (McGraw-Hill networks, 2018)
Chp1: Americans, Citizenship, and Governments -- Chp2: The American Colonies and their Government -- Chp3: The Constitution -- Chp4: The Bill of Rights -- Chp5: The Legislative Branch -- Chp6: The Executive Branch -- Chp7: The Judicial Branch -- Chp8: Political Parties -- Chp9: Voting and Elections -- Chp10: Public Opinion and Government -- Chp11: State Government -- Chp12: Local Government -- Chp13: Dealing With Community Issues -- Chp14: Citizens and the Law -- Chp15: Civil and Criminal Law -- Chp16: Introduction to Economics -- Chp17: The American Economy -- Chp18: Personal Finance -- Chp19: Business in America -- Chp20: Government's Role in the Economy -- Chp21: The Government and Banking -- Chp22: Financing the Government -- Chp23: International Trade and Economic Systems -- Chp24: The United States and Foreign Affairs